Organizational Culture, Leadership Style, and Organizational Communication on Organizational Performance: A Systematic Literature Review - Serly, Serly; Viasco, David Candra; Aritonang, Julius Dermawan; Anggiani, Sarfilianty; Aseanty, Deasy (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study systematically investigates the influence of organizational culture, leadership style, and organizational communication on organizational performance using a Systematic Literature Review (SLR) approach. These three dimensions are widely acknowledged as crucial for effectiveness and productivity. Organizational culture establishes shared values and norms that guide behavior and collaboration, while organizational communication connects structures, processes, and individuals, enabling coordination. Leadership style reflects how leaders inspire and direct subordinates toward common goals. The findings show that a strong, adaptive organizational culture, transformational leadership, and open, participatory communication are positively associated with enhanced organizational performance. The integration of these variables generates synergy in decision-making, employee engagement, and achievement of strategic objectives. Transformational leadership fosters innovation and motivation, whereas culture and communication provide the foundation for collaboration, cohesion, and sustainable outcomes. Methodologically, the study applies to a structured SLR combining bibliometric mapping and in-depth content analysis. Seventy peer-reviewed articles published between 2010 and 2024 were rigorously selected from indexed databases such as Scopus and Web of Science. The results emphasize that culture, leadership, and communication interact as reinforcing mechanisms that collectively strengthen organizational performance across diverse contexts.